Vedolizumab affects antibody responses to immunisation selectively in the gastrointestinal tract: randomised controlled trial results. Issue 1 (24th April 2014) - Wyant, Tim; Leach, Tim; Sankoh, Serap; Wang, Yuemei; Paolino, Jonathan; Pasetti, Marcela F; Feagan, Brian G; Parikh, Asit
Abstract : Objective: The α4 β7 integrin monoclonal antibody vedolizumab is hypothesised to be gut selective. Effects of vedolizumab on immune responses to parenterally or enterally administered antigens were investigated. Design: In this randomised, double-blind, placebo-controlled, phase I trial, healthy participants received a single intravenous dose of vedolizumab 750 mg (n=64) or placebo (n=63). After 4 days, participants began intramuscular hepatitis B vaccine (HBV; days 4, 32, 60) and oral cholera vaccine (OCV; days 4, 18) regimens. The study was designed to demonstrate a 15% non-inferiority margin for the between-group difference in the primary end point: percentage of participants with HBV seroconversion at day 74 (serum hepatitis B surface antigen (HBs) antibody titre ≥10 IU/L). OCV seroconversion at day 74 (>4-fold increase in serum cholera toxin (CT) antibodies) was a secondary end point. Results: A total of 56 (90.3%) placebo-treated and 54 (88.5%) vedolizumab-treated participants responded to HBV. Geometric mean anti-HBs titres were similar for placebo (114.4 IU/L) and vedolizumab (129.6 IU/L) at day 74. A total of 60 (96.8%) placebo-treated and 52 (82.5%) vedolizumab-treated participants responded to OCV at day 74. Geometric mean anti-CT IgG levels were higher for placebo than for vedolizumab at day 74 (9210.08 vs 3007.8 ELISA Units (EU)/mL) and day 32 (11629.3 vs 1575.4 EU/mL). Anti-CT IgA results were similar. Adverse events were consistent with previous experience. One serious adverse event (spontaneous abortion) was reported for placebo. Conclusions: Vedolizumab did not alter the response to parenterally administered antigens but reduced the response to oral antigens, demonstrating its gut-selective mechanism of action. Trial registration number: NCT Number: 01981616; EudraCT Number: 2011-001874-24.